2016
DOI: 10.1007/s10856-016-5825-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of laser-melted Mg–Sn–Zn alloys for biomedical application

Abstract: The rapid degradation rate of Magnesium (Mg) alloy limits its biomedical application even though it possesses outstanding biological performance and biomechanical compatibility. In this study, a combined method of laser rapid melting and alloying Zinc (Zn) was proposed to decrease the degradation rate of Mg-Sn alloy. The microstructure, degradation behaviors and mechanical properties of the laser-melted Mg-5Sn-xZn (x = 0, 2, 4, 6 and 8 wt.%) alloys were investigated. The results indicated that the grain size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
2
13
0
1
Order By: Relevance
“…4) show that the secondary phases are not continuous webs in the grain boundaries but instead occur in discontinuous form. Therefore, the corrosion resistance properties obtained in the present study are better than those reported in the literature [14,15,17,34]. In another similar study regarding the effect of secondary phases on corrosion resistance [14], corrosion rates were applied to Mg-Sn alloys containing different amounts of Sn.…”
Section: Evaluation Of Weight Loss Measurementsmentioning
confidence: 38%
See 3 more Smart Citations
“…4) show that the secondary phases are not continuous webs in the grain boundaries but instead occur in discontinuous form. Therefore, the corrosion resistance properties obtained in the present study are better than those reported in the literature [14,15,17,34]. In another similar study regarding the effect of secondary phases on corrosion resistance [14], corrosion rates were applied to Mg-Sn alloys containing different amounts of Sn.…”
Section: Evaluation Of Weight Loss Measurementsmentioning
confidence: 38%
“…In a similar study, there was evidence that the formation of a finer grain in the microstructure increases the corrosion resistance [15]. According to another study [40], microstructural parameters, such as phase distribution and grain size, affect the degradation behaviour of Mg-based alloys.…”
Section: Evaluation Of Weight Loss Measurementsmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, Mg-Sn alloys have been recognized as potential heat-resistant Mg alloys with an engineering application value in recent years [4][5][6]. Meanwhile, since the Sn element is an essential trace element in the human body and noncytotoxic, Mg-Sn alloys are promising bio-Mg alloys used as a bio-implant material [7,8]. Therefore, the study of Mg-Sn alloys is of essential research value.…”
Section: Introductionmentioning
confidence: 99%